PS-BPB03-5: DEVELOPMENT OF A THERAPEUTIC VACCINE FOR DYSLIPIDEMIA AND RELATED DISEASES TARGETING ANGIOPOIETIN-LIKE PROTEIN 3 (ANGPTL3). (January 2023) - Fukami, Hirotaka; Morinaga, Jun; Nakagami, Hironori; Kuwabara, Takashige; Morishita, Ryuichi; Oike, Yuichi; Mukoyama, Masashi
Abstract : Background: Dyslipidemia is a major factor in the development and progression of atherosclerotic diseases. Among dyslipidemias, familial hypercholesterolemia (FH) is a genetic disorder affecting approximately 34 million people worldwide, with 300, 000 patients in Japan. Since homozygous FH in particular is resistant to existing therapies, there is an urgent need to develop new therapies to reduce the risk of cardiovascular disease (CVD) in patients with FH. Design and Method: We focused on angiopoietin-like protein 3 (ANGPTL3) as a novel therapeutic target for dyslipidemia. ANGPTL3 is known to inhibit lipoprotein lipase as well as angiogenesis. Mutations of this gene in humans were reported to have no apparent pathogenic effects and have been reported to reduce triglyceride (TG) and LDL cholesterol (LDL-C) levels in the blood and the risk of developing CVD. We have developed a peptide vaccine that induces anti-ANGPTL3 antibodies and produces a potent therapeutic effect on dyslipidemia. We vaccinated ob/ob mice, an obese mouse model of type 2 diabetes, with a total of three doses of vaccine every two weeks and analyzed the results. Results: The vaccine group (n = 12) showed significant reductions in blood TG concentration by 52%, LDL-C concentration by 41%, and small dense LDL-C concentration by 49% compared to the control group (n = 10). In addition, histologically fatty liver was improved, and analysis of TG accumulation in hepatocytes showed a 47% reduction in the vaccine group. Furthermore, vaccination reduced dyslipidemia and atherosclerosis in ApoE function-deficient mice, a model of severe familial hypercholesterolemia. Notability, the vaccine did not induce cytotoxic immunity against the mouse liver and ANGPTL3-producing organs. Conclusions: Based on these results, this vaccine is expected to be one of the effective treatments for atherosclerotic diseases.